Factors Supporting Independence of Children during Transition to School. Theoretical Overview - Anastasiya K. Nisskaya; Arina S. Chuvilina (Вопросы образования)
Among the challenges faced by first-graders at the beginning of schooling, a special place is occupied by the development of independence, including in learning activities. It requires cognitive initiative, the ability to independently plan, predict and implement learning activities, to control and evaluate them. At the same time, the skills of independence (everyday, communicative, cognitive) developed in preschool age can be leveled in the case of a difficult transition to school.